cyp51A mutations, protein modeling, and efflux pump gene expression reveals multifactorial complexity towards understanding Aspergillus section Nigri azole resistance mechanism - Pooja Sen; Mukund Vijay; Himanshu Kamboj; Lovely Gupta; Jata Shankar; Pooja Vijayaraghavan (Scientific Reports, 2024)
Abstract Black Aspergillus species are the most common etiological agents of otomycosis, and pulmonary aspergillosis. However, limited data is available on their antifungal susceptibility profiles and associated resistance mechanisms. Here, we determined the azole susceptibility profiles of black Aspergillus species isolated from the Indian environment and explored the potential resistance mechanisms through cyp51A gene sequencing, protein homology modeling, and expression analysis of selected genes cyp51A, cyp51B, mdr1, and mfs based on their role in imparting resistance against antifungal drugs. In this study, we have isolated a total of 161 black aspergilli isolates from 174 agricultural soil samples. Isolates had variable resistance towards medical azoles; approximately 11.80%, 3.10%, and 1.24% of isolates were resistant to itraconazole (ITC), posaconazole (POS), and voriconazole (VRC), respectively. Further, cyp51A sequence analysis showed that non-synonymous mutations were present in 20 azole-resistant Aspergillus section Nigri and 10 susceptible isolates. However, Cyp51A homology modeling indicated insignificant protein structural variations because of these mutations. Most of the isolates showed the overexpression of mdr1, and mfs genes. Hence, the study concluded that azole-resistance in section Nigri cannot be attributed exclusively to the cyp51A gene mutation or its overexpression. However, overexpression of mdr1 and mfs genes may have a potential role in drug resistance.